Alarmin Cytokines as Central Regulators of Cutaneous Immunity - Hasegawa, Tatsuya; Oka, Tomonori; Demehri, Shadmehr (Frontiers in Immunology, 2022)
Skin acts as the primary interface between the body and the environment. The skin immune system is composed of a complex network of immune cells and factors that provide the first line of defense against microbial pathogens and environmental insults. Alarmin cytokines mediate an intricate intercellular communication between keratinocytes and immune cells to regulate cutaneous immune responses. Proper functions of the type 2 alarmin cytokines, thymic stromal lymphopoietin (TSLP), interleukin (IL)-25, and IL-33, are paramount to the maintenance of skin homeostasis, and their dysregulation is commonly associated with allergic inflammation. In this review, we discuss recent findings on the complex regulatory network of type 2 alarmin cytokines that control skin immunity and highlight the mechanisms by which these cytokines regulate skin immune responses in host defense, chronic inflammation, and cancer.